Deixis Analysis Of Webtoon Comic Your Letter By Hyeon A Cho - Mile Adhelia, Refina; Weddha Savitri, Putu; Wayan Mulyawan, I (Jurnal Ilmiah Wahana Pendidikan, 2026)
Deixis is a linguistic term that functions as referring to or showing something based on the context by using a word. This study aims to find the types of deixis, analyze the functions of each deixis, and identify how context of situation can strengthen the type and the function of deixis in the webtoon comic “Your Letter” by Hyeon A Cho by applying the theory of deixis by Levinson (1983) and the theory of context of situation by Halliday and Hasan (1991). The data were collected from the webtoon comic “Your Letter” by Hyeon A Cho. This study is deskwork research that employs purposive sampling, a non-probability technique. The data were collected using note-taking techniques. A qualitative method and content analysis technique are used to analyze the data found in this study. The data analysis is presented in a descriptive narrative format and an informal method. It is presented using a textual form or a collection of words. The results showed that all deixis types are present in the webtoon, each functions as pointing to the speaker, the addressee, and the third person, time and the location of the event, the portion of the ongoing discourse itself, social relationship. Furthermore, the study revealed that the context of situation explains how those deictic words function dynamically within field, tenor, and mode. The field helps to explain how deixis helps represent a clear background of the utterances. The tenor helps to clarify how deixis encodes the speaker, addressee, and the third-person relation of each participant, as well as the role of each participant. The mode helps to show how deixis is strengthened through expression and speech.